Tax Revenue: Account Representative Competency and Taxpayer Compliance - Yanuarius Sarbunan; Retna Safriliana; Suprapti Suprapti (University of Merdeka Malang, 2023)
This research was conducted with the aim of knowing whether Account Representative Competence and taxpayer compliance have an effect on tax revenue at KPP Pratama Mojokerto. Taxes are one of the largest state revenues, therefore the DJP as a government institution appointed to manage taxes wants to increase state revenues from the tax sector. One way is to increase tax recipients. It is hoped that the increase in tax revenues will have an impact on increasing state revenues. The research method is descriptive statistical analysis, data quality test, classical assumption test, and hypothesis testing. The independent variables in this study are Account Representative Competence and Taxpayer Compliance, the Dependent Variable is Tax Revenue. The total population in this study is 33 Account Representatives using the total sampling technique or saturated sample in which the entire population is sampled. Thus, the research sample in this study was 33 Account Representatives. The type of data used is primary data. The result of the research is that Account Representative competence partially does not have a significant effect on tax revenue, partial taxpayer compliance has a significant effect on tax revenue. Account Representative competence and taxpayer compliance simultaneously or together have a significant effect on taxpayer compliance